Reconstructing the image of transformative resistance against white hegemony in Richard Wright’s selected works - Wan Mazlini binti othm an, Moh an Ad Ghalim Glayl, (Opción, 2020)
This study aims at exploring the reconstructing the image of transformative resistance against white hegemony Richard Wright’s The Outsider, Uncle Tom’s Children and The Long Dream. It examines Richard’s deviation from the traditional depiction of the blacks’ resistance into a more subversive literary register reviling the oppressive white hegemony in the course of the selected novels. It is revealed that the analysis of colonial oppressive domination will be elaborated by applying Guy Poitras’ concept of hegemony; and its contradictory opposition will be interpreted through Ben Baer’s concept of deracinate resistance.